(untitled) (Research, Society and Development, 2024)
This article aims to report the implementation of the virtual telemedicine outpatient clinic for the pre-anesthetic evaluation of patients who will undergo surgical procedures at the Hospital das Clínicas of the Federal University of Pernambuco (HC-UFPE/EBSERH). The experience report type study, carried out at the E-Health Unit of HC-UFPE/EBSERH. Using the Management Application for University Hospitals that has the telemedicine and telehealth platform, this includes all patients seen during the period from December 2022 to December 2023 in the anesthesiology telemedicine agenda. Data collection was through the telehealth platform, only using the number of teleconsultations, without using any sensitive patient data. The results obtained during the 12-month period were 876 teleconsultations in the virtual anesthesiology outpatient clinic. Thus, it is concluded that the implementation of anesthesiology teleconsultations promotes greater assistance to patients and thus reduces the suspension of surgical procedures due to lack of adequate preparation of these patient.